Financial network (FiNe): a web application to assist investors in avoiding herding behaviour in stock market - Bahaludin, Hafizah; Abdullah, Mimi Hafizah; Mohammad, Nurul Farahain; Razali, Azaima (IIUM Press, 2022)
Herding behaviour is one of the behavioural phenomena that can be observed among investors in the financial markets. Generally, investors feel more secure if they copy and follow other investors. Regardless of the market's performance, Investors are focused on their own personal and confidential information, rather than relying on publicly available market data. During market stress, herding will be more common. Investors herding together would cause market imbalances and stock prices may deviate from their fundamental values as a result of the herding phenomenon. To avoid herding behaviour among investors, a web application of financial network (FiNe) is developed to assist investors in making informed decisions quickly in order to select stocks for their portfolios based on their own analyses rather than solely relying on what other investors are doing. FiNe application displays an interactive financial network that visualizes the relationship between stocks in which the input is based on closing prices of stocks. In addition, it is also able to display financial networks for different filters such as duration and sectorial basis. With the relationships between stocks displayed in the network, investors are able to run a quick analysis and financial information on stocks for portfolio selection.